"Pieces of life" - Tajana's growing up in Sunčana Škrinjarić's trilogy Ulica predaka [The Street of Ancestors], Ispit zrelosti [Test of Maturity] and Bijele strijele [White Arrows] - Batinić, Ana (Array, 2021)
This paper analyses the growing up of Tajana, a fictional character in unhealthy family surroundings as depicted in Sunčana Škrinjarić’s (1931 – 2004) trilogy: The Street of Ancestors (1980), Test of Maturity (2002), and White Arrows (2004). The main controversy of the trilogy is the presentation of a childhood without didacticism, moral lessons, or idealization; a childhood which is more unhappy than protected and joyful. By breaking settled rules and taboos, Škrinjarić created her own, recognizable style of narration. This study will particularly focus on Tajana’s relationship with her mother and the girl’s emotional development, which can be interpreted in light of childhood trauma. Tajana’s mother is an educated, beautiful, and coquettish woman who does not love her daughter. She sees the girl only as a “redundant little brat”, a reminder of her broken first marriage, and an obstacle to happiness in life. Hitting Tajana, pulling her hair, and essentially ignoring all her needs, she can be labelled a bad mother who fails to fulfil the duties of her role: being present and protective, as well as providing for her daughter’s well-being and upbringing. Tajana’s experience of emotional neglect and emotional and even physical abuse from her mother in her childhood results in the girl’s problems in building firm and healthy relationships in her adult life.